Inside the Host: Understanding the Evolutionary Trajectories of Intracellular Parasitism - Bartošová-Sojková, Pavla; Butenko, Anzhelika; Richtová, Jitka; Fiala, Ivan; Oborník, Miroslav; Lukeš, Julius (Annual review of microbiology, 2024)
This review explores the origins of intracellular parasitism, an intriguing facet of symbiosis, where one organism harms its host, potentially becoming deadly. We focus on three distantly related groups of single-celled eukaryotes, namely Kinetoplastea, Holomycota, and Apicomplexa, which contain multiple species-rich lineages of intracellular parasites. Using comparative analysis of morphological, physiological, and molecular features of kinetoplastids, microsporidians, and sporozoans, as well as their closest free-living relatives, we reveal the evolutionary trajectories and adaptations that enabled the transition to intracellular parasitism. Intracellular parasites have evolved various efficient mechanisms for host acquisition and exploitation, allowing them to thrive in a variety of hosts. Each group has developed unique features related to the parasitic lifestyle, involving dedicated protein families associated with host cell invasion, survival, and exit. Indeed, parallel evolution has led to distinct lineages of intracellular parasites employing diverse traits and approaches to achieve similar outcomes.
Keywords: symbióza; Apicomplexa; intracellular parasite; parazitární nemoci; Host-Parasite Interactions; fylogeneze; interakce hostitele a parazita; comparative analysis; Phylogeny; Eukaryota; Kinetoplastida; Parasitic Diseases; biologická evoluce; adaptation; genomic features; parallel evolution; Animals; lidé; Biological Evolution; Humans; zvířata; Microsporidia; Symbiosis; symbiosis